2020
DOI: 10.1302/1863-2548.14.200148
|View full text |Cite
|
Sign up to set email alerts
|

Effective dose of radiation per screw in surgery of adolescent idiopathic scoliosis: Matched pair analysis of 293 pedicle screws inserted using three different techniques

Abstract: Purpose Reports on heterogenous groups of patients have indicated that pedicle screw insertion guided by navigation (PIN) leads to, for the patient, higher doses of radiation compared with pedicle screw insertion guided by fluoroscopy (PIF). This would be a major concern, especially in paediatric deformity correction. Methods After a power analysis (aiming at > 0.8) 293 pedicle screws which were inserted in patients with adolescent idiopathic scoliosis were analyzed by comparing effective dose and fluorosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In the adaptive multiobjective differential evolution stage, each submultimedia image is treated as a slice/ adaptive multiobjective differential evolution technology of H.265/HEVC [8][9][10]. As shown in Figure 1, each submultimedia image is treated as a slice/adaptive multiobjective differential evolution technology of H.265/HEVC.…”
Section: Adaptive Multiobjective Differential Evolution Algorithmmentioning
confidence: 99%
“…In the adaptive multiobjective differential evolution stage, each submultimedia image is treated as a slice/ adaptive multiobjective differential evolution technology of H.265/HEVC [8][9][10]. As shown in Figure 1, each submultimedia image is treated as a slice/adaptive multiobjective differential evolution technology of H.265/HEVC.…”
Section: Adaptive Multiobjective Differential Evolution Algorithmmentioning
confidence: 99%
“…The accuracy of PS placement based on navigation system has been reported in pediatric spinal deformities [11,14]. The accuracy of PS placement has been reported not only in adolescent idiopathic scoliosis but also in neuromuscular scoliosis.…”
Section: Discussionmentioning
confidence: 99%
“…Pedicle screws (PS) and iliac screws (IS) have been extensively used in pediatric spinal deformities to improve correction of the deformity and obtain rigid fixation [5][6][7][8]. In recent years, there have been many reports on the effective use of preoperative computed tomography (CT) navigation (pCTN) and intraoperative CT navigation (iCTN) for PS and IS placement, owing to their its safety and low radiation exposure [6,7,[9][10][11][12][13][14]. On the other hand, there are reports of posterior corrective fusion to the pelvis using PS and IS for spinal deformity associated with myelomeningocele [2,3], however, there are no reports regarding placement of PS, conventional IS, subcrestal IS, or sacral alar IS (SAIS) using a navigation system.…”
Section: Introductionmentioning
confidence: 99%
“…Since some of our patients were operated by navigation based on a preoperative CTS, we used these CTS images as recumbent imaging technique in this investigation and found that CTS may be applied to classify scoliotic minor curves as structural or non-structural. We presently avoid performing any more pedicle screw insertions guided by navigation (PIN) with preoperative CTS in AIS patients because of the higher exposure to radiation of the patients, but applying navigation by an intraoperative 3D scan [18]. For the same reason, we now aspire to apply different recumbent imaging techniques, i.e., MRI or intraoperative images, as "replacement" for BR.…”
Section: Discussionmentioning
confidence: 99%